Students’ Perceptions of and Responses to Oral Podcast Feedback on Their Writing - Correa-Pérez, Roxanna (2025)
Introduction. This study proposes an approach to developing English writing skills through oral feedback delivered via podcast. Feedback is regarded as a fundamental component of the academic writing learning process. In particular, feedback provided on writing tasks has been the focus of extensive research, such as that conducted by Christiansen and Bloch (2016) and Sommers (2013). We suggest that personalized attention can be achieved through oral feedback via podcasts. Some authors indicate that audio feedback triggers a sense of connectivity between the teacher and the student (Kirwan et al., 2023). Aim. The aim of this research was to investigate students’ perceptions and actions towards the use of podcasts as a method of receiving feedback. Methodology. This is qualitative research. The data collected were the perceptions and actions of university students on their writing tasks in an English as a Foreign Language (EFL) class. The participants were 26 university students majoring in English as a second language and taking a course that included process writing. A semi-structured interview was conducted with the participants to gather their perceptions and actions after receiving oral feedback via podcast. Results. The results indicated that the participants valued and considered detailed and precise oral feedback. They expressed positive feelings about the tone of the teacher’s voice and the direct relationship between the feedback received and the task.